Genetic diversity and connectivity of the Ostreid herpesvirus 1 populations in France: A first attempt to phylogeographic inference for a marine mollusc disease. Issue 1 (23rd April 2022) - Delmotte, Jean; Pelletier, Camille; Morga, Benjamin; Galinier, Richard; Petton, Bruno; Lamy, Jean-Baptiste; Kaltz, Oliver; Avarre, Jean-Christophe; Jacquot, Maude; Montagnani, Caroline; Escoubas, Jean-Michel
Abstract: The genetic diversity of viral populations is a key driver of the spatial and temporal diffusion of viruses; yet, studying the diversity of whole genomes from natural populations still remains a challenge. Phylodynamic approaches are commonly used for RNA viruses harboring small genomes but have only rarely been applied to DNA viruses with larger genomes. Here, we used the Pacific oyster mortality syndrome (a disease that affects oyster farms around the world) as a model to study the genetic diversity of its causative agent, the Ostreid herpesvirus 1 (OsHV-1) in the three main French oyster-farming areas. Using ultra-deep sequencing on individual moribund oysters and an innovative combination of bioinformatics tools, we de novo assembled twenty-one OsHV-1 new genomes. Combining quantification of major and minor genetic variations, phylogenetic analysis, and ancestral state reconstruction of discrete traits approaches, we assessed the connectivity of OsHV-1 viral populations between the three oyster-farming areas. Our results suggest that the Marennes-Oléron Bay represents the main source of OsHV-1 diversity, from where the virus has dispersed to other farming areas, a scenario consistent with current practices of oyster transfers in France. We demonstrate that phylodynamic approaches can be applied to aquatic DNA viruses to determine how epidemiological, immunological, and evolutionary processes act and potentially interact to shape their diversity patterns.